2019
DOI: 10.1103/physrevd.100.104035
|View full text |Cite
|
Sign up to set email alerts
|

Screened fifth forces mediated by dark matter-baryon interactions: Theory and astrophysical probes

Abstract: We derive the details of a new screening mechanism where the interactions of baryons and dark matter can be screened according to the local dark matter density. In this mechanism, the value of Newton's constant is dark matter density-dependent, allowing for the possibility that astrophysical phenomena are very different in galaxies less dense than the Milky Way. The parameterized post Newtonian parameter γ, which quantifies the difference between kinematical and lensing probes, also depends on dark matter dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 116 publications
(201 reference statements)
0
23
0
Order By: Relevance
“…Modified gravity theories are able to simultaneously drive the acceleration of the cosmic expansion (dark energy) while remaining compatible with solar system tests of gravity [44][45][46][47]. They are also leading candidates for explaining the Hubble tension [48][49][50]. Their success is due to screening mechanisms, which suppress fifth forces in high density environments.…”
Section: Gw190521mentioning
confidence: 99%
“…Modified gravity theories are able to simultaneously drive the acceleration of the cosmic expansion (dark energy) while remaining compatible with solar system tests of gravity [44][45][46][47]. They are also leading candidates for explaining the Hubble tension [48][49][50]. Their success is due to screening mechanisms, which suppress fifth forces in high density environments.…”
Section: Gw190521mentioning
confidence: 99%
“…Their numerical relation is converted to an approximate expression in Ref. [23] as L ∝ G 1.46 . Since there is no consensus on the precise nature of supernovae physics, as a second case we also use the distance modulus derived from this luminosity-G dependence:…”
Section: A Type Ia Supernovaementioning
confidence: 99%
“…1) or acceleration, for example. Recently Sakstein, Desmond, and Jain (2019) identified a new screening mechanism that screens fifth forces mediated by interactions between dark matter and baryons. They suggest several astrophysical tests that merit further investigation.…”
Section: B Future Directions For Theorymentioning
confidence: 99%
“…This coupling could lead to cosmic acceleration at late times (Berezhiani, Khoury, and Wang, 2017;Ferreira et al, 2018). Sakstein, Desmond, and Jain (2019) investigated this model and showed that it contains a novel screening mechanism where the value of Newton's constant can vary depending on the local dark matter density. They also list further potential astrophysical tests that could prove fruitful once the theory is developed; see also Desmond, Jain, and Sakstein (2019) and Desmond and Sakstein (2020).…”
Section: B Future Directions For Theorymentioning
confidence: 99%
See 1 more Smart Citation